Identifying an optimal lymph node yield for penile squamous cell carcinoma: prognostic impact of surgical dissection. (26th August 2019) - Chipollini, Juan; Azizi, Mounsif; Lo Vullo, Salvatore; Mariani, Luigi; Zhu, Yao; Ye, Ding W.; Ornellas, Antonio Augusto; Watkin, Nick; Ager, Michael; Hakenberg, Oliver; Heidenreich, Axel; Raggi, Daniele; et al.
Abstract : Objective: To evaluate the prognostic impact of lymph node yield (LNY) on survival outcomes for penile squamous cell carcinoma (SCC). Patients and methods: In all, 532 patients who underwent inguinal LN dissection (ILND) across tertiary referral centres from Europe, China, Brazil and North America were retrospectively evaluated. From this cohort, 198 patients received pelvic LND (PLND).We identified threshold values for ILND and PLND using receiver operating characteristic curves. We tested prognostic value of LNY for recurrence‐free survival (RFS), disease‐specific survival (DSS), and overall survival (OS) using the Kaplan–Meir method and Cox proportional hazard regression models. Results: The median (interquartile [IQR]) age was 59 (49–68) years and the median (IQR) follow‐up after ILND was 28 (12–68.2) months. Overall, 85% of the patients had bilateral dissections. The median (IQR) number of inguinal LNs removed was 15 (10–22). Of those receiving PLND, The median (IQR) number of LNs was 13 (8–19). A LNY of ≥15 was used for dichotomisation of ILND patients, and a LNY of ≥9 was used in the PLND cohort. Patients with a LNY ≥15 had significantly better 5‐year OS vs patients with a LNY <15 (70.1% vs 58.7%). On multivariable analyses, a LNY ≥15 was a predictor of OS (hazard ratio [HR] 0.68, P = 0.029). For cN0 patients, a LNY ≥15 was an independent predictor of RFS (HR 0.52, P = 0.043) and OS (HR 0.53, P = 0.021). In the PLND cohort, a LNY ≥9 was a predictor of RFS (HR 0.53, P = 0.032). Conclusions: Using one of the largest LND datasets to date, we found LNY to be a significant predictor of outcomes after lymphatic staging for penile SCC. Prospective validation is warranted.